2017
DOI: 10.1289/ehp89
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Cancer and Water Disinfection By-product Exposures through Multiple Routes: A Population-Based Case–Control Study (New England, USA)

Abstract: Background:Ingestion of disinfection byproducts has been associated with bladder cancer in multiple studies. Although associations with other routes of exposure have been suggested, epidemiologic evidence is limited.Objectives:We evaluated the relationship between bladder cancer and total, chlorinated, and brominated trihalomethanes (THMs) through various exposure routes.Methods:In a population-based case–control study in New England (n=1,213 cases; n=1,418 controls), we estimated lifetime exposure to THMs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 26 publications
0
43
1
4
Order By: Relevance
“…We used pooled data for 3,481 cases and 5,977 controls from 7 case-control studies included in a meta-analysis by Costet et al (2011) to derive the continuous exposure-response function that was the basis of our country-specific ORs for bladder cancer in association with country-specific mean THM estimates. Although this is the most comprehensive pooled analysis currently available, it is limited to case-control studies and does not include a recent U.S. study of 1,213 bladder cancer cases and 1,418 controls (Beane Freeman et al 2017).…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…We used pooled data for 3,481 cases and 5,977 controls from 7 case-control studies included in a meta-analysis by Costet et al (2011) to derive the continuous exposure-response function that was the basis of our country-specific ORs for bladder cancer in association with country-specific mean THM estimates. Although this is the most comprehensive pooled analysis currently available, it is limited to case-control studies and does not include a recent U.S. study of 1,213 bladder cancer cases and 1,418 controls (Beane Freeman et al 2017).…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…Our analyses are based on men and women combined. While most of the case-control studies included in the pooled analysis report a null or inverse association among women, there are also case-control studies showing higher risks in women than men (Beane Freeman et al 2017). Future studies may want to consider comparing estimates based on sex-specific exposure-response functions to estimates for men and women combined.…”
Section: Countrymentioning
confidence: 99%
“…It has been suggested that the byproducts of water disinfection such as chlorinated and brominated trihalomethanes (THMs) may increase the risk of bladder cancer. This risk was evaluated in a recent population-based case-control study from the National Cancer Institute in the United States [33]. This showed a weak association between drinking water with high levels of THMs and bladder cancer (OR 1.53, 95%CI: 1.01-2.32).…”
Section: Environmentmentioning
confidence: 99%
“…However, epidemiological research has reported associations between adverse health effects and the presence of disinfection byproducts in tap water at concentrations that generally meet applicable national drinking water standards [3]. Multiple studies have reported an increased risk of bladder cancer in association with exposure to drinking water disinfection byproducts [4][5][6], and the risk of other cancers has been suggested [7,8]. Birth defects [9] and miscarriages [10] have also been linked to disinfection byproducts.…”
Section: Introductionmentioning
confidence: 99%